2021
DOI: 10.48550/arxiv.2110.13780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-Terminal Tandem Solar Cells based on Perovskite and Transition Metal Dichalcogenides

Abstract: Perovskite solar cells have shown power conversion efficiencies (PCE) comparableto cystalline silicon solar cell despite involving low-temperature, solution based synthesis processes outside clean room environment. As the theoretical PCE of a perovskite solar cell with band gap 1.55 eV is capped to 33 % due to Shockley-Queisser limit, tandem configurations are being investigated to go beyond this limit. Here, we propose a two-terminal (2T) tandem solar cell structure consisting of perovskite and multilayer tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A simulation study employing solar cell capacitance simulator (SCAPS 1D) tool indicated that a 2-T perovskite-TMD TSC configuration consisting of MAPbI 3 as the top-cell absorber and MoTe 2 as bottom cell absorber can yield a PCE of 35.3% under AM 1.5G solar radiation spectrum. [78] A TSC configuration with MAGeI 3 as the top-cell absorber material and MoTe 2 as the bottom cell absorber material when modeled with SCAPS 1D exhibited a PCE of 27.09% and 35.11% for the 2-T and 4-T heterojunction configurations, respectively. [69] A 2-T TSC formed of MAPbI 3 perovskite Cu 2 ZnSn(S,Se) 4 (kesterite) as absorber layers for two subcells provided a PCE of 20%.…”
Section: Tscsmentioning
confidence: 99%
“…A simulation study employing solar cell capacitance simulator (SCAPS 1D) tool indicated that a 2-T perovskite-TMD TSC configuration consisting of MAPbI 3 as the top-cell absorber and MoTe 2 as bottom cell absorber can yield a PCE of 35.3% under AM 1.5G solar radiation spectrum. [78] A TSC configuration with MAGeI 3 as the top-cell absorber material and MoTe 2 as the bottom cell absorber material when modeled with SCAPS 1D exhibited a PCE of 27.09% and 35.11% for the 2-T and 4-T heterojunction configurations, respectively. [69] A 2-T TSC formed of MAPbI 3 perovskite Cu 2 ZnSn(S,Se) 4 (kesterite) as absorber layers for two subcells provided a PCE of 20%.…”
Section: Tscsmentioning
confidence: 99%
“…The recombination layer of the 2-T tandem device is introduced to establish the current matching condition between the MAGeI 3 and the TMD cells. The purpose of introducing a recombination layer in monolithic 2T tandem configurations is to recombine the carriers from the ETL and HTL by establishing the current Parameter FTO [23][24][25] IGZO [26] CuO [27] ZnO [28][29][30] ITO [23][24][25] MAGeI 3 [31][32][33] MoTe 2 [ 34,35] Cu 2 Te [34,35] Thickness matching condition between the MAGeI 3 and the TMD cells. [37] The recombination layer should be chosen such that the electrical losses especially the voltage loss should be minimum with the requirement of a suitable work function to collect the charge carriers generated.…”
Section: Impact Of the Thickness Of The Recombination Regionmentioning
confidence: 99%